ALPK1 Accelerates the Pathogenesis of Osteoarthritis by Activating NLRP3 Signaling. (22nd August 2022) - Liu, Xin; Zhao, Jie; Jiang, Henghua; Guo, Huilin; Li, Yingjie; Li, Huimin; Feng, Yaping; Ke, Jin; Long, Xing
ABSTRACT: Alpha‐kinase 1 (ALPK1), a member of the alpha‐kinase family, has been shown to be involved in mediating inflammatory responses and is strongly associated with gout; however, its modulatory role in osteoarthritis (OA) remains unclear. Here, we uncovered elevation of ALPK1 in degraded cartilage of destabilized medial meniscus (DMM) and collagenase‐induced osteoarthritis (CIOA), two different mouse OA models induced by mechanical stress or synovitis. Intraarticular administration of recombinant human ALPK1 (rhALPK1) in vivo exacerbated OA pathogenesis in both DMM and CIOA mice, whereas ALPK1 knockout reversed this process. In vitro study demonstrated that ALPK1 aggravates metabolic disturbances in chondrocytes by enhancing the production of NOD‐like receptor protein 3 (NLRP3), an inflammasome sensors driving interlukin‐1β (IL‐1β)‐mediated inflammatory conditions. Furthermore, the selective inhibition of nuclear factor‐κB (NF‐κB) or NLRP3 indicates that NLRP3 is a downstream signaling governed by NF‐κB in ALPK1‐activated chondrocytes. Collectively, these results establish ALPK1 as a novel catabolic regulator of OA pathogenesis, and targeting this signaling may be a promising treatment strategy for OA. © 2022 American Society for Bone and Mineral Research (ASBMR).